Final report: monetary and fiscal policy - Katarzyna Zukrowska; Dominik Sobczak; Massimiliano Marzo (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
This report reflects on recent trends in fiscal and monetary policies at the onset of EU-enlargement. Particularly, the authors focus on necessary adjustment processes for future EU-members. How to smooth best the transition period between normal EU-accession and eventual participation in the Eurozone? Having conducted empirical regional reports, the Ezoneplus research consortium combines the results in two main parts: Katarzyna Zukrowska and Dominik Sobczak reveal trends and risks in fiscal policy issues, such as divergent consolidation policies in Western Europe, possible lessons for CEE countries and the importance of the Stability and Growth Pact. Then, Massimiliano Marzo elaborates a comprehensive picture of the impact of monetary policy, especially inflation targeting in three CEE countries.
Keywords: E5; F4; E61; E65; 330; EU-budget costs; ECB; EMU; EU-enlargement; fiscal and monetary policy; heterogeneity; Stability and Growth Pact; Monetary Policy Modelling